The Urgency of Strengthening Historical Emphaty in Historical Learning: A Review of Bibliometric Analysis - Kusnoto, Yuver; Supriatna, Nana; Wiyanarti, Erlina; Hasan, Said Hamid (AL-ISHLAH: Jurnal Pendidikan, 2024)
Strengthening an empathetic attitude towards past events is crucial, particularly in the educational context. This study investigates four key areas: (1) the growth of international publications on historical empathy within the Scopus database from 2002 to 2023; (2) the core journals that focus on historical empathy research; (3) the productivity of researchers in this field; and (4) the development of research on historical empathy based on co-words and co-authors. Data were collected from Scopus using keywords related to history and empathy, focusing on publications from 2002 to 2023. The analysis, conducted using VosViewer software, revealed that although the number of publications on historical empathy has remained relatively small, it has steadily increased each year. A total of 132 articles have been published, primarily by researchers from the United States and the United Kingdom. This study provides valuable insights for history educators and researchers by highlighting the trends in historical empathy research, which is particularly relevant for teaching and learning history in academic settings.